RETRACTED: AFAP1-AS1 Promotes Epithelial-Mesenchymal Transition and Tumorigenesis Through Wnt/β-Catenin Signaling Pathway in Triple-Negative Breast Cancer - Zhang, Kaiming; Liu, Peng; Tang, Hailin; Xie, Xiaoming; Kong, Yanan; Song, Cailu; Qiu, Xingsheng; Xiao, Xiangsheng (Frontiers in Pharmacology, 2018)
Long non-coding RNA (lncRNA) Actin filament-associated protein1-antisense RNA 1 (AFAP1-AS1) is overexpressed in various types of cancers and plays important roles in tumor progression and prognosis. This study investigates the role of AFAP1-AS1 in tumor progression in triple-negative breast cancer (TNBC). We found that AFAP1-AS1 was overexpressed in TNBC tissues and cells. Overexpression of lncRNA AFAP1-AS1 was associated with poor prognosis in TNBC patients. Moreover, we demonstrated that upregulation of AFAP1-AS1 promoted cell proliferation and invasion, and inhibited cell apoptosis in vitro, while overexpression of AFAP1-AS1 promoted tumor growth in vivo. Our results also revealed that upregulation of AFAP1-AS1 activated Wnt/β-catenin pathway to promote tumorigenesis and cell invasion by increasing the expression of C-myc and epithelial-mesenchymal transition related molecules in TNBC. Collectively, AFAP1-AS1 can be an independent prognostic biomarker and an effective therapeutic target of triple- negative breast cancer.